Analisis Requirement Engineering pada Integrasi Pasca-Merger Sistem Biller Message Switching dan Aggregator - Devina, Fakhira; Raharjo, Teguh; Nabasya, Oristania Wahyu; Hendry, Darell (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Information system integration is one of the crucial activities in Post-Merger Integration (PMI). Information system integration must be carried out with careful planning so that the objectives of mergers and acquisitions can be achieved. Therefore, it is necessary to collect needs from each stakeholder to define the scope and approach of the integration that will be carried out. This research aims to understand the phenomenon of integration project management of the Biller Message Switching and Aggregator system happened on the XYZ Financial Institution's Post-Merger Integration (PMI) activity. The research method is analysis descriptive using the Post-merger Integration Specific Requirements Engineering model to describe the integration process in 3 phases, namely the initial assessment phase, decision and planning, and execution. The research results show that all three entities’ systems have different system specifications and architecture. New system architecture decisions are determined from dependencies on the existing system and the number of billers served. The implementation of the new system is carried out based on the results of previous planning and involves billers to socialize the migration system services. This research provides input for the information systems integration process in the company's merger and acquisition process so that it is carried out systematically and structured.